SEKILAS MENGENAI KONTEKS WARGA NEGARA DAN KEWARGANEGARAAN: ASPEK DAN TANTANGAN - Juminah, Juminah; Fardila, Vinny (JURNAL DIALOKA: Jurnal Ilmiah Mahasiswa Dakwah dan Komunikasi Islam, 2022)
At a glance about the context of citizenship, both in terms of aspects and challenges, namely concluding that citizenship learning has entered the independent curriculum, that is, they or their children must learn lessons according to their own abilities and knowledge. In addition, a learning approach is needed in which educator activities select learning activities that are effective and efficient as well as fun in achieving certain goals. In addition, developments in this era of globalization have changed the habits of society in general. Whether it impacts for good or bad. For example, to society's work pattern which requires using digital technology in almost all aspects of work. Society must anticipate the impact caused by the increase in global population. Prepare and assert yourself so that you can face problems in the future and not fall into organizations/communities that can be detrimental to yourself. Many great women are born today and become a motivation for society. Those are some of the challenges that society must face today.